Biodiversity utilization and conservation / (Acc. 4504) - Arunachalam, A. (Ayyanadar), 1970-; Arunachalam, K. (Kusum); Pedam, R.; Pangging, G. (Jaipur : Aavishkar Publishers, Distributors, 2008)
With reference to Northeast India.
Keywords: Forests and forestry; Biodiversity conservation